Application of Double Difference Tomography Method to Determine The 3D Seismic Wave Velocity Structure of GoLF Geothermal Field - Kana N. Naamin; David P. Sahara; Andri D. Nugraha; Irvan Ramadhan (Jurnal Geofisika, 2018)
GoLF geothermal eld is located in South Solok Regency, 150 km SE of Padang city, West Sumatra.Geology, geochemistry and geophysical surveys had been conducted since 2008. Geophysical survey which had been performed including microseismic and magnetotelluric surveys. Seismic velocity structure modelling need to be conducted in order to characterize geothermal reservoir.This study uses microseismic data recorded from 36 seismometers which installed in two time recording time ranges; from September 2010 to April 2011 and from September 2012 to December 2013, with microseismic events recorded respectively 135 and 2692 events. To maximize the result of picking waveform, the data is processed using the Master Event Cross Correlation method to update the catalog data and get more accurate arrival time. Furthermore, the author used TomoDD software to produce hypocenter relocation and the 3D velocity structure under GoLF's geothermal reservoir. The results of the 3D velocity model can be used to determine the structure and phase of the fluid under GoLF geothermal field.